Archaeological Research on Guardhouse No. 5 at Westerplatte: The Site of the Defenders’ Death at the Military Transit Depot - Dziewanowski, Adam; Garlicki, Przemysław; Jarzęcka-Stąporek, Joanna; Kalka, Piotr (Social consequences of war, 2024)
In 2021, the Archaeological Department of the Museum of the Second World War in Gdańsk conducted archaeological research of the relics of Guardhouse No. 5 at Westerplatte. The works were carried out as part of the 7th stage of archaeological research on the peninsula, which began in 2016. Within excavation No. 12, relics of the lower storey of the guardhouse were uncovered, which allowed to determine the exact location and size of the building and to reconstruct the layout and function of individual rooms. During the works, several human bones were found – the remains of Polish soldiers who were in the building when German Luftwaffe bombs destroyed it on September 2, 1939. At least seven Polish defenders died in the rubble of the guardhouse. During the examination of the building, 4,645 artefacts (of the highest scientific and exhibition value) were found, for which a separate field inventory of artefacts was kept. Within the excavation no. 12, the remains of a reinforced fence made of Ledóchowski’s mesh and a partially preserved shell-pit from a German 50 kg bomb from September 2, 1939 were also documented. A fragment of the western wall of the upper storey of the guardhouse was found in the shell-pit fill. The remains of the guardhouse no. 5 and the foundations of the reinforced fence made of Ledóchowski’s mesh are now exhibited in the form of a permanent ruin in the access zone to the new military cemetery of Polish Army soldiers at Westerplatte, which was opened on November 4, 2022. Ten defenders of the Military Transit Depot are buried in the new cemetery. Most of them died in the bombed guardhouse No. 5.